2010
DOI: 10.1089/ten.tec.2009.0596
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton Imaging and Quantitative Analysis of Collagen Production by Chondrogenic Human Mesenchymal Stem Cells Cultured in Chitosan Scaffold

Abstract: We used the combined imaging modality of multiphoton autofluorescence and second-harmonic generation microscopy to investigate the chondrogenic process of human mesenchymal stem cells cultured in chitosan scaffold. Isolated human mesenchymal stem cells seeded onto chitosan scaffold were induced to undergo chondrogenesis by addition of the transforming growth factor-β3. After continuous culturing, the engineered tissues at the same scaffold location were imaged at different time points for up to 49 days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…7A). 83,84 Also, mesenchymal stem cells embedded in various environments such as silk, 85 chitosan, 86 acellular scaffolds, 87 and rat skin 88 were monitored using two-or multiphoton fluorescence microscopy.…”
Section: Optical Imagingmentioning
confidence: 99%
“…7A). 83,84 Also, mesenchymal stem cells embedded in various environments such as silk, 85 chitosan, 86 acellular scaffolds, 87 and rat skin 88 were monitored using two-or multiphoton fluorescence microscopy.…”
Section: Optical Imagingmentioning
confidence: 99%
“…In a study by Chen et al [109], the selected chitosan scaffold material showed strong AF that could be applied for the study of cell-biomaterial rsif.royalsocietypublishing.org J R Soc Interface 10: 20130263 interactions (described in §3.3.1). Rice et al [119] characterized silk fibroin (in the form of fibres, scaffolds, hydrogels and films) and studied the effect of hydration/dehydration, gelation time and biomechanical treatment (compression and stretching) on the autofluorescence (and SHG) signals.…”
Section: Autofluorescence Imagingmentioning
confidence: 99%
“…a 420/20 filter when excitation occurs at 840 nm). Figure 8a shows an interesting approach for long-term monitoring and quantifying tissue morphogenesis by a combined 2-PF/SHG approach [109]. Scaffold and cells were imaged by two-photon AF and collagen I with SHG (both excited at 760 nm).…”
Section: Imaging Cellular Proteinsmentioning
confidence: 99%
“…Type I, III, IV collagen are produced at high levels in wounds that are exposed to chitin-based biomaterials [40]. Similar effects were reported when chitosan scaffolds were used to culture connective tissue [41], ligaments [42], or stem cells [43]. In addition to collagen, the synthesis of other ECM components, such as glycosaminoglycans, are also increased by chitosan [44].…”
Section: Discussionmentioning
confidence: 55%